Social Justice And Development - Through The Lens Of Right To Education Movement In India - Gupta, Konark Pratap; Kashyap, Vinay Kumar (International Journal of Psychosocial Rehabilitation, 2020)
The idea of ’development’ has been conceptualized in many forms. The mainstream discourse around the idea has been focussed on development as economic growth. In the Sixties, through Dependency theory1 efforts were made to bring the idea of justice to forefront in development discourse but it was short lived. Domestic and international organizations focused more and more on poverty alleviation for decades and did not try to integrate ’justice’ in development studies or goals. This conception of development as economic growth has been now critiqued as rooted in western worldview. It was criticized because of the unexamined assumptions and insensitivity towards the expectations, requirements and values of the ’developing’ world. The real living conditions of people were not given any importance. Despite the criticism, core interests of developmental studies still remained unchallenged for the most part. ’Social justice’ has occupied a significant role in philosophical, political and legal discourses since the beginning of politico-legal philosophy but it’s integration in the discourse on development is still in nebulous stage. Scholars like Amartya Sen and Martha Nusbaum have made major contribution in integrating the idea of justice in development discourse. The approach suggested in this paper is an expansion of those ideas. The conception of the term ’development’ needs to be revisited and must reflect the idea of social justice. To establish this, the paper will provide justification for choosing the right to education movement as a case study, establish relationship between education social justice and development and finally answer why is it that the idea of ’social justice’ that needs to be part of development discourse.